2020
DOI: 10.1029/2020ja028037
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Length Scales of Periodic Mesoscale Density Structures in the Solar Wind Over Two Solar Cycles

Abstract: It is now well established through multiple event and statistical studies that the solar wind at 1 AU contains contains periodic, mesoscale (L ∼ 100–1,000 Mm) structures in the proton density. Composition variations observed within these structures and remote sensing observations of similar structures in the young solar wind indicate that at least some of these periodic structures originate in the solar atmosphere as a part of solar wind formation. Viall et al. (2008, https://doi.org/10.1029/2007JA012881) anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 59 publications
4
52
0
Order By: Relevance
“…The spectral analysis of the magnetic field at the geostationary orbit and ground revealed that the interaction of the magnetosphere with solar wind periodic density structures resulted in a global modulation of the magnetosphere at the longer time scales associated with each PDS, as well as ULF waves at discrete frequencies. Kepko et al (2020) identified PDSs in solar wind measurement from the Wind spacecraft over two solar cycles. In a conservative estimate, they determined a PDS occurrence rate of ≈60% in the slow solar wind and ≈30% in the fast solar wind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral analysis of the magnetic field at the geostationary orbit and ground revealed that the interaction of the magnetosphere with solar wind periodic density structures resulted in a global modulation of the magnetosphere at the longer time scales associated with each PDS, as well as ULF waves at discrete frequencies. Kepko et al (2020) identified PDSs in solar wind measurement from the Wind spacecraft over two solar cycles. In a conservative estimate, they determined a PDS occurrence rate of ≈60% in the slow solar wind and ≈30% in the fast solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…The PDSs manifest in the solar wind as density fluctuations at frequencies typically below 4.0 mHz. At nominal solar wind speeds, the PDSs correspond to structures with size scales of the order of the Earth's magnetosphere (Kepko et al., 2020 ). The resultant directly driven ULF waves, observed in the magnetosphere and at the ground, occur at similar frequencies falling within and extending beyond the Pc5 band (Birch & Hargreaves, 2020 ; Hartinger et al., 2014 ; Kepko et al., 2002 ; Kepko & Spence, 2003 ; Stephenson & Walker, 2002 ; Viall et al., 2009 ; Villante et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Longer-period variations-more than about 16 min-of magnetospheric fields and plasma are also observed, typically in association with external drivers including solar wind dynamic pressure structures (Agapitov & Cheremnykh, 2013;Kepko & Spence, 2003). These mesoscale structures, near-ubiquitous features advecting with the solar wind (Kepko et al, 2020;Viall et al, 2009), likely originate at or near the Sun, possibly in association with the formation of the slow solar wind (Kepko et al, 2016;Viall & Vourlidas, 2015). They tend to be grouped into discrete-scale sizes, with observed frequency a function of this size and the solar wind speed (Kepko & Spence, 2003;Viall et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These periodic solar-wind structures were first identified by examining the solar wind at Earth when spacecraft in the magnetosphere indicated that the magnetosphere was undergoing periodic compressions (Kepko et al, 2002); the solar-wind periodic structures are also responsible for periodic variations of the total electron content of the Earth's ionosphere (Birch and Hargreaves, 2020a). Periodic density oscillations are found typically in slow solar wind with periods in the range of 4-140 min, corresponding to radial wavelengths of 8 × 10 4 -3 × 10 6 km (Viall et al, 2008;Kepko et al, 2020), which are in the inertial range of scalesizes. Viall et al (2009b) reports a periodicstructure interval wherein the alpha-to-proton number-density ratio α/p oscillates with the proton number density: the ion composition α/p variation is a firm indication that the numberdensity oscillation has its origin at the Sun.…”
Section: Periodic Density Structuresmentioning
confidence: 99%